2014
DOI: 10.1007/s00410-013-0961-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and rheological controls on the formation of mafic enclaves or banded pumice

Abstract: Magma mixing can occur in a fluid manner to produce banded pumice or in a brittle manner to form enclaves. We propose that the critical control on mixing style is a competition between developing networks of crystals in the intruding magma that impart a strength to the magma and melting and disrupting those networks in the host. X-ray computed tomography analysis demonstrates that banded pumice from the 1915 Mt. Lassen eruption lacks crystal networks. In contrast, rhyodacite hosts with mafic enclaves from Chao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…The formation of the trachytic enclave within the syenite may be directly related to the emplacement of a new magma batch derived from a deeper trachytic reservoir. Enclave formation follows fragmentation of a cooled dike by convection within the still partially molten syenite body (Andrews and Manga 2014). This may also explain why the enclavehosting syenite sample has high 87 Sr/ 86 Sr, as that portion of syenite would have been affected by magmatic and hydrothermal fluids related to the trachyte dyke emplacement episode.…”
Section: Plumbing System Model: "Nest Volcano"mentioning
confidence: 98%
“…The formation of the trachytic enclave within the syenite may be directly related to the emplacement of a new magma batch derived from a deeper trachytic reservoir. Enclave formation follows fragmentation of a cooled dike by convection within the still partially molten syenite body (Andrews and Manga 2014). This may also explain why the enclavehosting syenite sample has high 87 Sr/ 86 Sr, as that portion of syenite would have been affected by magmatic and hydrothermal fluids related to the trachyte dyke emplacement episode.…”
Section: Plumbing System Model: "Nest Volcano"mentioning
confidence: 98%
“…Typically, magma mixing/mingling occurs during replenishment by a mafic magma of a felsic and mushy reservoir [8][9][10][11][12][13][14] , either deep or shallow, which, in the latter case, may trigger a volcanic eruption 8 . The injection of denser basalt into a lighter reservoir most likely produces viscous gravity currents spreading at the floor, leading to a stratified two-layer system 15 , except when excess momentum is available, which may induce fountaining 16 .…”
mentioning
confidence: 99%
“…Ensuing crystallization can lead to density inversion producing either local 17,18 or wholesale 19 overturning and associated mixing/mingling, depending on viscosity contrast 20 . Observations and fluid dynamical considerations [8][9][10][11][12][13][14][15][16][17][18][19][20][21] have shown that, in calcalkaline reservoirs, mixing/mingling most likely starts either from such boundary layer instabilities 17 , with centimetre to decimetre wavelength scale 18 , or from breakup of injected magma dykes 12 . These mechanisms readily explain enclave sizes as observed in plutonic or volcanic rocks 18,21 , that is, mingled magmas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vernon 2014; Clemens and Bezuidenhout 2014). The convective rise of the hybrid conduit to form mingled magmas (Snyder and Tait 1996;Clynne 1999;Andrews and Mang 2014) and buoyant rise of hybrid magma blobs that become enclaves suspended within the enclosing host granitic magma at emplacement level (e.g. Vernon 1984;Clynne 1999;Coombs et al 2003).…”
Section: The Late Triassic Akazishan Plutonmentioning
confidence: 99%